From Isolation to Pilot-Scale Production: Enterococcus faecium YC07 with Urate-Lowering Potential from Fermented Food Jiangshui - Xiaoyu Cao; Qianqian Xu; Yu Zhang; Hai Yan (Foods)
Hyperuricemia arises from urate overproduction and/or underexcretion. Probiotics offer the potential for alleviating hyperuricemia by degrading urate precursors. This study characterized Enterococcus faecium YC07 isolated from the traditional Chinese fermented food Jiangshui, which demonstrated efficient biodegradation of nucleosides (urate precursors), converting 2.0 g/L to nucleobases within 48 h. Whole genome sequencing revealed a 2.53 Mb draft genome (59 contigs, 38.21% GC content) containing 2387 protein-coding genes. Genomic and phenotypic analysis confirmed its probiotic potential, including high tolerance of simulated gastric fluid (98.89% survival) and intestinal fluid (44.51% survival), and strong adhesion capacity (24.16% auto-aggregation, 35.48% hydrophobicity), pathogen inhibition, and antioxidant activity. The identified antibiotic resistance genes and virulence factors were assessed alongside acute oral toxicology, cytotoxicity, antibiotics susceptibility, hemolysis, and enzymatic activity assays, confirming safety. Furthermore, successful pilot-scale fermentation in a 100 L fermenter demonstrated industrial feasibility. These findings established E. faecium YC07 as a safe and effective probiotic candidate for functional foods targeting hyperuricemia management.